22 - Running While Others Walked: Remembering Thandika Mkandawire - Rama Salla Dieng; Adebayo Olukoshi (CODESRIA Bulletin, 2021)
Rama Salla Dieng* interviews Adebayo Olukoshi** on the life and work of Thandika Mkandawire. Olukoshi shares memories of how Thandika helped to shape development thinking in Africa and beyond. Initially published in ROAPE: http://roape.net/2020/04/27/running-while-others-walked-remembering-thandika-mkandawire Rama Salla Dieng Centre of African Studies, University of Edinburgh Adebayo Olukoshi Director, IDEA (Africa and West Asia office)